2013
DOI: 10.1136/bmjopen-2013-002560
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of EGFR and KRAS mutations in non-small cell lung cancer (NSCLC): routine screening data for central Europe from a cohort study

Abstract: ObjectivesOwing to novel therapy strategies in epidermal growth factor receptor (EGFR)-mutated patients, molecular analysis of the EGFR and KRAS genome has become crucial for routine diagnostics. Till date these data have been derived mostly from clinical trials, and thus collected in pre-selected populations. We therefore screened ‘allcomers’ with a newly diagnosed non-small cell lung carcinoma (NSCLC) for the frequencies of these mutations.DesignA cohort study.SettingLung cancer centre in a tertiary care hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
118
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 31 publications
16
118
2
3
Order By: Relevance
“…A previous study on TKI-sensitive NSCLC indicated that a mutation in the EGFR tyrosine kinase domain is responsible for activating various anti-apoptotic signaling pathways (14). An EGFR mutation may be detected in 43-89% of patients with lung cancer; mutations on exons 19 and 21 are the most common (15). These mutations have been observed to confer increased cell sensitivity to TKIs, including to icotinib (3).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on TKI-sensitive NSCLC indicated that a mutation in the EGFR tyrosine kinase domain is responsible for activating various anti-apoptotic signaling pathways (14). An EGFR mutation may be detected in 43-89% of patients with lung cancer; mutations on exons 19 and 21 are the most common (15). These mutations have been observed to confer increased cell sensitivity to TKIs, including to icotinib (3).…”
Section: Discussionmentioning
confidence: 99%
“…These results have led to a consensus that the presence of EGFR mutations is a strong predictor of TKI treatment response and various associations and working groups, internationally and in Poland, now recommend screening newly diagnosed patients with advanced NSCLC for specific mutations in order to customize the modality of treatment (9,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Despite these, the incidence rates of EGFR mutations are found to vary substantially between different regions and countries (8,10,15). Possible reasons for this discrepancy could be lack of clarity in selection criteria for EGFR-positivity testing, differences in molecular methods employed for screening, and issues with sampling and tissue preservation.…”
Section: Predictors Of Egfr Mutation and Factors Associated With Clinmentioning
confidence: 99%
“…These cause a loss in autoinhibition of the tyrosine kinase and a continually activated state of its kinase function. Deletion in exon 19 and a L858R (leucine to arginine substitution at position 858) substitution in exon 21 comprise approximately 90% of EGFR mutations found in adenocarcinomas of the lung (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Patients with diagnosed mutations in EGFR are referred to as EGFR-positive.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 2 × 106 HCC827, HCC827/ ER, siNEDD4-, or EV-infected HCC827/ER cells were subcutaneously injected into the mouse skin under the left lower quadrants, respectively. When tumor volumes reached about 100-150 mm 3 , these mice were treated with intragastric administration of erlotinib (60 mg/kg) for 2 weeks once a day. Tumor sizes were measured every 3 days.…”
Section: In Vivo Experimentsmentioning
confidence: 99%